COMPETITION BETWEEN HETEROGENEOUS AGENTS IN COMPLEX ENVIRONMENT - Owczarek, Tomasz (International Journal of Computing, 2014)
The article applies complexity theory to study hete rogeneous organizations in an environment filled with their competitors and complementors. An agent-based simulation model is used to analyze effects of interactions in an environment with different level of complexity. Agents, differing in size a nd adaptability, try to adapt to fitness landscape they are placed in (which is based on Kauffman’ s NK model) in order to increase their fitness level. Results of conducted simulations are presented and analyzed.